2004
DOI: 10.1128/iai.72.7.3987-4003.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Two Murein Lipoproteins ofSalmonella entericaSerovar Typhimurium Contribute to the Virulence of the Organism

Abstract: Septic shock due to Salmonella and other gram-negative enteric pathogens is a leading cause of death worldwide. The role of lipopolysaccharide in sepsis is well studied; however, the contribution of other bacterial outer membrane components, such as Braun (murein) lipoprotein (Lpp), is not well defined. The genome of Salmonella enterica serovar Typhimurium harbors two copies of the lipoprotein (lpp) gene. We constructed a serovar Typhimurium strain with deletions in both copies of the lpp gene (lpp1 and lpp2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
111
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(119 citation statements)
references
References 89 publications
(92 reference statements)
7
111
1
Order By: Relevance
“…One potential set of virulence factors that has received relatively little attention is the pathogen's considerable assemblage of lipoproteins. Lipoproteins have long been recognized as virulence determinants in a variety of bacterial pathogens, and a number of them have been developed into vaccine immunogens (Fortney et al, 2000;Hayashi & Wu, 1990;Schwan et al, 1995;Sha et al, 2004). Lipoproteins are anchored to the inner or outer membrane through a covalently linked lipid moiety (Babu et al, 2006;Hantke & Braun, 1973;Inouye et al, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…One potential set of virulence factors that has received relatively little attention is the pathogen's considerable assemblage of lipoproteins. Lipoproteins have long been recognized as virulence determinants in a variety of bacterial pathogens, and a number of them have been developed into vaccine immunogens (Fortney et al, 2000;Hayashi & Wu, 1990;Schwan et al, 1995;Sha et al, 2004). Lipoproteins are anchored to the inner or outer membrane through a covalently linked lipid moiety (Babu et al, 2006;Hantke & Braun, 1973;Inouye et al, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial lipoproteins are established bacterial virulence factors [11–13,24,26,36] that function as inflammatory stimulants in infection and disease progression. Our study is the first to show pro-inflammatory effects of AaPAL, an outer membrane lipoprotein of a major periodontal pathogen, A. actinomycetemcomitans .…”
Section: Discussionmentioning
confidence: 99%
“…However, current interest concerning Gram-negative infections is increasingly focused on bacterial outer membrane proteins (OMPs), especially lipoproteins [10]. In fact, recent studies have suggested that bacterial lipoproteins are major players in inflammatory reactions caused by pathogenic species, such as Shigella flexneri, Brucella abortus , and Salmonella enterica [11–13]. Regarding A. actinomycetemcomitans , 23 different lipoproteins are detectable among the proteins secreted by A. actinomyctemcomitans biofilm [14], but their bioactivity is poorly understood [15–17].…”
Section: Introductionmentioning
confidence: 99%
“…Maturation of Lpp requires modification of the lipid moiety, which is catalyzed by enzymes, specifically glycerol transferase, O-acyl transferase, signal peptidase II, and N-acyl transferase [8]. Two functional copies of the lpp gene (designated as lppA and lppB) exist on the chromosome of S. Typhimurium 14028 located in tandem and separated by 82 bp [9]. Deletion of both copies of the lpp gene results in a S. Typhimurium mutant that is minimally invasive to epithelial cells, non-motile, and severely impaired in its ability to induce cytotoxicity in murine macrophages (RAW 264.7 cells) and T84 human colonic epithelial cells, possibly due to the reduced production of proinflammatory cytokines and chemokines (e.g., tumor necrosis factor-alpha [TNF-α] and interleukin [IL]-8) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Two functional copies of the lpp gene (designated as lppA and lppB) exist on the chromosome of S. Typhimurium 14028 located in tandem and separated by 82 bp [9]. Deletion of both copies of the lpp gene results in a S. Typhimurium mutant that is minimally invasive to epithelial cells, non-motile, and severely impaired in its ability to induce cytotoxicity in murine macrophages (RAW 264.7 cells) and T84 human colonic epithelial cells, possibly due to the reduced production of proinflammatory cytokines and chemokines (e.g., tumor necrosis factor-alpha [TNF-α] and interleukin [IL]-8) [9]. The lpp (lppAB) double knockout (DKO) mutant was avirulent in mice following oral and intraperitoneal (i.p.)…”
Section: Introductionmentioning
confidence: 99%